2016
DOI: 10.1103/physrevb.94.220201
|View full text |Cite
|
Sign up to set email alerts
|

On the disorder-driven quantum transition in three-dimensional relativistic metals

Abstract: The Weyl semimetals are topologically protected from a gap opening against weak disorder in three dimensions. However, a strong disorder drives this relativistic semimetal through a quantum transition towards a diffusive metallic phase characterized by a finite density of states at the band crossing. This transition is usually described by a perturbative renormalization group in d = 2 + ε of a U (N ) Gross-Neveu model in the limit N → 0. Unfortunately, this model is not multiplicatively renormalizable in 2+ε d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 44 publications
(53 reference statements)
3
59
0
Order By: Relevance
“…Various of these transitions have been suggested to belong to the universality class defined by the chiral transition appearing in the 3D GrossNeveu (GN) model [7] well-known in the context of highenergy physics and conformal field theories [17,18]. This applies, in particular, to the interaction-induced transition toward a charge density wave of electrons on the 2D honeycomb lattice that breaks the (Ising) sublattice symmetry [7], or the disorder-driven transition toward a diffusive metal in a 3D Weyl semi-metal [15]. …”
mentioning
confidence: 99%
“…Various of these transitions have been suggested to belong to the universality class defined by the chiral transition appearing in the 3D GrossNeveu (GN) model [7] well-known in the context of highenergy physics and conformal field theories [17,18]. This applies, in particular, to the interaction-induced transition toward a charge density wave of electrons on the 2D honeycomb lattice that breaks the (Ising) sublattice symmetry [7], or the disorder-driven transition toward a diffusive metal in a 3D Weyl semi-metal [15]. …”
mentioning
confidence: 99%
“…Indeed, we have recently showed that the consistent description of the transition with SR disorder beyond two loops involves an infinite number of relevant operators generated by the RG flow. To overcome this obstacle we proposed an alternative way based on a 4 − ε expansion [21]. However, generalization of this approach to the case of LR disorder is a non trivial task which remains to be done.…”
Section: Fig 4 Sr Transitionmentioning
confidence: 99%
“…In particular, the transition is characterized through the critical exponents ν and z: at this transition, the correlation length diverges as ξ ∼ |∆ − ∆ c | −ν where ∆ c is the critical disorder strength, while the dynamic critical exponent z is defined trough the scaling between energy and momenta at the transition ω ∼ k z . Besides, it was found that exactly at the transition the wave functions and local DOS exhibit multifractality similar to the Anderson transition but with different universality classes [21,23].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations